Myopericarditis after the Pfizer mRNA COVID-19 vaccine in adolescents - Schauer, J.; Buddhe, S.; Colyer, J.; Sagiv, E.; Law, Y.; Mallenahalli Chikkabyrappa, S.; Portman, M. A. (The Journal of Pediatrics, 2021)
The FDA extended the emergency use authorization of the Pfizer-BioNTech mRNA COVID-19 vaccine for adolescents 12 through 15 years of age on May 10, 2021[1]. Following authorization large numbers of adolescents across the country began to receive immunization. As of June 21, 2021, 98,008 adolescents 12 through 15 years of age and 69,489 adolescents 16 and 17 years of age in Washington state completed the 2-dose schedule of mRNA COVID-19 vaccine [[2]].Reports of post-COVID-19 vaccine myocarditis and pericarditis have emerged , particularly after the second dose of the mRNA vaccines. Initial cases were noted predominantly in male adolescents and young adults in the Israeli military[[3]]. Subsequently, U.S. institutions have reported 7 cases in adolescents over 16 years old[[4]] and 7 cases in young adults [[5]]. As the age range of eligibility for the COVID-19 vaccine broadened in Washington state we have cared for a cohort of younger patients with post-vaccine myopericarditis. We describe clinical and cardiac MRI (CMR) findings for 13 patients 12 through 17 years of age cared for in our center.